Knowledge of Sexually Transmitted Infections Among Women of Reproductive Age at Samarinda City - Nurachma, Evy; Siregar, Nursyahid; Syamsiah, Syamsiah (International Journal Labs, 2023)
exually Transmitted Infections (STIs) are a significant global health issue that deserves more attention, considering their long-term negative impact on the quality of future generations. Having a good understanding of STIs plays a crucial role in preventing their spread. This study aims to evaluate the knowledge of reproductive-aged women regarding Sexually Transmitted Infections (STIs) in the Loa Bakung Primary Health Center area, Samarinda City, East Kalimantan Province. The research method employed was quantitative, with data collection conducted through interviews and questionnaires. The participants involved in this study are reproductive-aged women visiting the Loa Bakung Primary Health Center. The results of the univariate analysis indicate that the majority of respondents have a higher level of education and a good understanding of STIs. However, there are still some respondents with limited understanding. The majority of respondents also do not experience STIs. Bivariate analysis reveals a significant correlation between the level of knowledge about STIs and the occurrence of STIs. The majority of STI cases occur among respondents with lower levels of knowledge.